Prevalence of dengue, Zika and chikungunya viruses in Aedes (Stegomyia) aegypti (Diptera: Culicidae) in a medium-sized city, Amazon, Brazil - Fred Júlio Costa Monteiro; Fábio Rodrigo Paixão Mourão; Edicelha Soares D’Athaide Ribeiro; Marlisson Octávio da Silva Rêgo; Pablo Abdon da Costa Frances; Raimundo Nonato Picanço Souto; Marlucia dos Santos Façanha; Roozbeh Tahmasebi; Antônio Charlys da Costa (Revista do Instituto de Medicina Tropical de São Paulo, 2020)
ABSTRACT Aedes aegypti is associated with epidemic diseases in Brazil, such as urban yellow fever, dengue, and more recently, chikungunya and Zika viruses infections. More information about Ae. aegypti infestation is fundamental to virological surveillance in order to ensure the effectiveness of control measures in use. Thus, the present study aims to identify and compare infestation and infectivity of Ae. aegypti females in Macapa city, Amapa State (Amazon region), Brazil, between the epidemiological weeks 2017/02 and 2018/20. A total number of 303 Ae. aegypti females were collected at 21 fixed collection points, 171 at the 10 collection points in the Marabaixo neighborhood and 132 at the 11 collection points in the Central neighborhood. Among the collected samples, only two were positive for dengue virus, with a 2.08% (2/96 pools) infectivity rate for Marabaixo. The difference between the medians of Ae. aegypti females captured in Central and Marabaixo sites was not statistically significant. The findings indicate similar mosquito infestation levels between the neighborhoods, and a low-level of mosquito infectivity, although dengue virus was found only in Marabaixo. Virological surveillance of Ae. aegypti was important to identify sites of infection and determine possible routes of transmission to enable health surveillance teams to adopt preventive strategies where infected mosquitoes are present and act faster.